THE RELATIONSHIP BETWEEN FASTING BLOOD GLUCOSE LEVELS AND ST- SEGMENT PATTERNS IN PATIENTS WITH ACUTE CORONARY SYNDROME AT KARSA HUSADA HOSPITAL INDONESIA: A CROSS-SECTIONAL STUDY - Riskiyah , Riskiyah; Rachmawati, Ermin; Tarsadi, Tarsadi; Ahdi, Iwal Reza; Saputra, Indra Wahyu; Maulana, Syafiq (Journal of Community Health and Preventive Medicine, 2026)
Interpreting severity of acute coronary syndrome (ACS) through an electrocardiogram (ECG) requires a high level of expertise. However, the limited number of medical personnel skilled in ECG interpretation in primary healthcare facilities in Indonesia often leads to delays in determining the initial treatment. Furthermore, fasting blood glucose (FBG) levels in ACS patients tend to be elevated and are associated with various ST-segment changes on the ECG, which are thought to play a significant role in determining the severity of ACS. This study aimed to analyze the relationship between FBG levels and the types of ST-segment patterns in patients with ACS. This study used an analytical observational research design. Data were obtained from patient medical records collected between January and June 2025. The sample size was determined using the Slovin formula, yielding a total of 100 participants who met the inclusion criteria. Eligible participants were patients diagnosed with ACS, aged 18 years or older, and possessing complete medical records that included ECG data interpreted by a cardiologist and laboratory results containing FBG levels. Blood samples and ECG recordings were collected in the morning at the Cardiovascular Care Unit. Relationships between variables were analyzed using non-parametric statistical methods, specifically the Chi-square test and the contingency coefficient. Most participants were male (64%) and aged 46–65 years (59%). The majority exhibited elevated FBG levels (71%) accompanied by ECG findings of ST-segment depression (44%). A significant relationship was found between FBG levels and the type of ST-segment pattern (p = 0.02, < 0.05), although the strength of the association was weak (Cramer’s V = 0.241). FBG levels are significantly associated with ST-segment patterns in patients with ACS and may serve as an early indicator for assessing the severity of myocardial ischemia.   KEYWORDS: acute coronary syndrome; electrocardiogram;  fasting blood glucose.